Biodegradation of diesel fuel by two psychrotolerant strains isolated from Southern Victoria Island, Antarctica - Abdul Habib, Nur Muhamad Syahir (2017)
Hydrocarbon contamination in Antarctica poses a great threat to the delicate and unique ecosystems of this continent. Bioremediation of hydrocarbon pollutants via utilisation of the indigenous hydrocarbon-degrading bacteria, has been proposed as an environmentally friendly method to clean-up contaminated soils in Antarctica. This study focused on diesel-degrading Pseudomonas and Rhodococcus species isolated from pristine soils located at the Southern Victoria Island, Antarctica. Isolates were assessed for their ability to grow on diesel as a sole carbon source on solid media at 4°C. Nine isolates showed significant growth in enriched agar after 14 days of incubation. Isolates were then screened to obtain the most promising diesel-degrading strains through colourimetric assay. Two potent isolates that possess rapid utilisation of 0.5% (v/v) diesel were selected and identified as Pseudomonas sp. strain ADL15 and Rhodococcus sp. strain ADL36. The factors that contribute to the growth of both strains were characterised initially using the conventional ‘one-factor-at-a-time’ approach. During this stage, the optimal condition for the growth of both ADL15 and ADL36 were at pH 7.0, 20°C, 1.0% (w/v) NaCl, and 1.0 g/L NH4NO3. However, strain ADL36 favoured a higher amount of diesel (2.0% (v/v)) for bacterial growth by comparison to ADL15 (1.0% (v/v)). Percentage of dodecane mineralisation was used as the mean to indicate diesel reduction through gas chromatographic analysis. While strain ADL36 showed 83.75% of dodecane mineralisation, the reduction of dodecane by AD15 is merely at 22.39%. Response surface methodology (RSM) based on central composite design (CCD) was used to improve and optimise the effect of significant factors toward the biodegradation of diesel. RSM proved to enhance the reduction of experimented hydrocarbon (dodecane) with a 15% and 16% increment of mineralisation for isolate ADL15 (38.32%) and ADL36 (99.89%), respectively. The results also demonstrated that addition of salt to culture media was the limiting factor in hydrocarbon degradation. Whole genome sequencing showed that ADL15 and ADL36 were closely related to the Pseudomonas fluorescens and Rhodococcus erythropolis grouping, respectively. Metagenomic analyses revealed the presence of alkane hydroxylases systems which was responsible for alkane degradation in ADL36 but not in ADL15. This founding corresponds to the gas chromatographic analysis in which ADL36 proved to be a better alkane degrader than ADL15. Detection of the complete pathway of aromatic compound degradation in the latter strain indicates a stronger inclination of the strain to utilise aromatic components in diesel as the carbon source. The presence of putative monooxygenases may also suggest that this strain may utilise specific alkane for their growth. The results from this study showed that strain ADL15 and ADL36 have an excellent potential in bioremediation of aromatics and aliphatics, respectively.